If nothing is done, attrition will remain a challenge: Lecturers’ experiences and perspectives on effective hybrid learning systems in open and distance learning terrain. - Rendani Sipho Netanda (Studies in Learning and Teaching, 2026)
Despite the adequate pervasiveness of hybrid learning systems in open and distance e-learning (ODeL) environments, student attrition remains a significant concern, impacting student success, retention, and institutional performance. This study investigates the lecturers’ experiences with the use and effectiveness of hybrid learning systems in reducing attrition rates in open and distance e-learning settings. The purpose of this study was to establish how the hybridization of in-person and e-learning approaches contributes to attrition in ODeL. The study was informed by the following research questions: What are lecturers’ experiences of hybrid learning systems in reducing attrition rates in open and e-learning institutions? What perceptions are there of lecturers towards increasing the effectiveness of hybrid learning systems? Data was collected from lecturers using in-depth interviews to determine their experiences of hybrid learning systems and correlations between hybrid learning modalities and attrition rates. Findings reveal that using hybrid learning systems effectively, coupled with a comprehensive support model, can improve student engagement and persistence and reduce attrition rates at lower postgraduate levels in ODeL by providing a flexible, supportive learning environment. The study provides valuable insights for lecturers, policymakers, and the management of ODeL institutions.